Healthcare providers’ narratives about interactionally troubling patient exchanges: Accounting for and against an active patient role - Elina Weiste; Melisa Stevanovic; Nanette Ranta; Henri Nevalainen (Qualitative Research in Medicine & Healthcare)
The current trend in healthcare is to actively involve patients in their own treatment; however, in practice, healthcare providers may adhere to paternalistic views, which may not align with ideals related to patient involvement. This tension may become visible when providers talk about service encounters that they experienced as being interactionally troubling. In this empirical qualitative study, we utilize Bamberg’s narrative positioning analysis to explore how healthcare providers construct patients’ roles in narratives about such troubling exchanges. Data consist of 20 audio-recorded interviews with healthcare providers. We found two types of narratives in which healthcare providers’ perceptions of interactionally troubling patient exchanges were consistently related to their implicit evaluations of patients along a continuum of activeness versus passiveness. In the first, an active patient was considered ideal, and the problematic patient was one who is passive. In the second, a patient’s over-activeness was thought to interfere with the healthcare delivery. While providers’ complaints about patient passiveness were unproblematically presented from the perspective of the patient participation ideal, complaints about patient over-activeness were difficult to account for due to their inherent connotations with paternalism. Thus, we conclude that there is a need for training and interventions aiming to develop healthcare providers’ critical awareness of shifting cultural models, including patient involvement ideals and providers’ capacity to reflect paternalistic tendencies.